1999
DOI: 10.1144/gsl.sp.1999.155.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Thrust-fracture network and hydrothermal gold mineralization: Witwatersrand Basin, South Africa

Abstract: This paper examines the geometry and genesis of a mineralized thrust-related fracture system, developed at a major rheological interface between Witwatersrand sediments and Ventersdorp volcanics in the Witwatersrand Basin of South Africa. At the Elandsrand Gold Mine, the conglomeratic Ventersdorp Contact Reef, which separates these successions, is imbricated by kilometre-wide zones of minor thrusts containing ultracataclastic fault rocks associated with hydrothermal fluid flow. Several sets of fractures are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…5), the wedging between Lower Wits shale-rich package and the overlying Ventersdorp metabasalt, unconformities, high strain zones in the heterogeneous lithological packages for 1-5 m above unconformities, shear zones (Mullins, 1989) and many small quartz veinlets (Phillips and Law, 2000). Newer data and more detailed interpretations support the model of fluid migration through fracture networks and thrust structures (Jolley et al, 1999(Jolley et al, , 2004, and the additional seismic interpretations confirm a network of structures on the scale of mines and goldfields (Beach and Smith, 2007;Dankert and Hein, 2010). Many of these structures are inferred to have been generated and active during the late Central Rand (Upper Wits) times, and others during post-Klipriviersberg Group-pre Platberg Group thrusting events.…”
Section: Channelways For Hydrothermal Fluidsmentioning
confidence: 58%
See 2 more Smart Citations
“…5), the wedging between Lower Wits shale-rich package and the overlying Ventersdorp metabasalt, unconformities, high strain zones in the heterogeneous lithological packages for 1-5 m above unconformities, shear zones (Mullins, 1989) and many small quartz veinlets (Phillips and Law, 2000). Newer data and more detailed interpretations support the model of fluid migration through fracture networks and thrust structures (Jolley et al, 1999(Jolley et al, , 2004, and the additional seismic interpretations confirm a network of structures on the scale of mines and goldfields (Beach and Smith, 2007;Dankert and Hein, 2010). Many of these structures are inferred to have been generated and active during the late Central Rand (Upper Wits) times, and others during post-Klipriviersberg Group-pre Platberg Group thrusting events.…”
Section: Channelways For Hydrothermal Fluidsmentioning
confidence: 58%
“…The Reno framework included a complex post-burial history of the Witwatersrand Basin including syn-sedimentary and post-sedimentary deformation of the Witwatersrand Supergroup with bedding parallel deformation (Berlenbach, 1995;Coward et al, 1995;Hilliard and McCourt, 1995;Jolley et al, 1999;McCarthy, 1994;Myers et al, 1990;Roering and Smit, 1987), and overturning of some Witwatersrand reefs was identified (Tweedie, 1986). Interpretation of seismic surveys led to an interpretation of large thrust faults in the footwall to goldfields (Coward et al, 1995;Fig.…”
Section: Pongola Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…Jolley et al 1999). For example, at the Revenge mine, mineralized shears exhibit evidence for early brittle slip events and brecciation, followed by ductile shearing during progressive potassic and carbonate alteration, gold precipitation and vein formation (Nguyen et al 1998).…”
Section: Deposit Styles In Mesothermal Gold Systemsmentioning
confidence: 99%
“…In detailed studies of the relationship between gold mineralization and small-scale structure, Jolley et al (1999Jolley et al ( , 2004 presented data and interpretations that overwhelmingly support a model for the structural control of gold mineralization in fracture networks and thrust structures generated during the late Central Rand Group and post Klipriviersberg Group-pre Platberg Group thrusting events. Those workers interpreted the fracture networks, which provide a linked fluid flow pathway through the rocks, as well as sites for gold precipitation, as being generated in the tip zones of larger thrust faults deeper in the section.…”
Section: Resultsmentioning
confidence: 96%